Analysis Antimicrobial Activity of Sumbawa White Honey against Staphylococcus aureus ATCC 25293 - Alamsyah, Abiel Dwi Cahya Firdaus; Hasbi, Nurmi; Rosyunita, Rosyunita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Staphylococcus aureus is one of the major bacteria causing health problems in humans, such as skin infections, abscesses, sepsis, pneumonia, endocarditis, and osteomyelitis. Methicillin-Resistant Staphylococcus aureus (MRSA) has been identified since 1990. Consequently, research into alternative antibiotics utilizing natural products is crucial, one of which is honey. Honey is chosen due to its antibacterial properties, including sugars, hydrogen peroxide, phenolic compounds, and others. This study aims to analyze the antibacterial activity of white honey from Sumbawa against S. aureus ATCC 25293. The research method employed was experimental in a laboratory setting using a post-test only control group design. The honey was processed by dilution, and antibacterial testing was conducted using the disc diffusion method at concentrations of 25%, 75%, 100%, with chloramphenicol as positive control and DMSO as negative control. The antibacterial test was repeated five times, and antibacterial activity was assessed by measuring the diameter of inhibition zones around the discs. The results showed inhibition zones for honey at concentrations of 25%, 75%, 100% measuring 1.33 mm, 4.60 mm, and 7.33 mm respectively. Based on these findings, it can be concluded that white honey from Sumbawa exhibits antibacterial activity of weak to moderate strength, but its effectiveness against S. aureus ATCC 25293 is relatively low. Further identification of antibacterial compounds in Sumbawa white honey is recommended for quantitative analysis.